2023
DOI: 10.1039/d3em00060e
|View full text |Cite
|
Sign up to set email alerts
|

Combining the targeted and untargeted screening of environmental contaminants reveals associations between PFAS exposure and vitamin D metabolism in human plasma

Abstract: We have developed, validated, and applied a method for targeted and untargeted screening of environmental contaminants in human plasma using liquid chromatography high-resolution mass spectrometry (LC-HRMS). The method was optimized...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It can be seen in Figure 1 that none of the PFAAs correlated with either 25(OH)D 3 or 1,25(OH) 2 D 3 : PFOS ( Figure 1 A,B), PFOA ( Figure 1 C,D), PFHxS ( Figure 1 E,F), and PFNA ( Figure 1 G,H). When PFOS, PFOA, PFNA, and PFHxS were correlated as a combined group for vitamin sufficiency (>20 ng/mL) and vitamin D deficiency (<20 ng/mL) [ 41 ], still no correlation with PFOS, PFOA, PFHxS, or PFNA was found. It can be seen in Figure 2 that none of the PFAAs correlated with either sufficient or deficient 25(OH)D 3 : PFOS ( Figure 2 A,B), PFOA ( Figure 2 C,D), PFHxS ( Figure 2 E,F), and PFNA ( Figure 2 G,H).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be seen in Figure 1 that none of the PFAAs correlated with either 25(OH)D 3 or 1,25(OH) 2 D 3 : PFOS ( Figure 1 A,B), PFOA ( Figure 1 C,D), PFHxS ( Figure 1 E,F), and PFNA ( Figure 1 G,H). When PFOS, PFOA, PFNA, and PFHxS were correlated as a combined group for vitamin sufficiency (>20 ng/mL) and vitamin D deficiency (<20 ng/mL) [ 41 ], still no correlation with PFOS, PFOA, PFHxS, or PFNA was found. It can be seen in Figure 2 that none of the PFAAs correlated with either sufficient or deficient 25(OH)D 3 : PFOS ( Figure 2 A,B), PFOA ( Figure 2 C,D), PFHxS ( Figure 2 E,F), and PFNA ( Figure 2 G,H).…”
Section: Resultsmentioning
confidence: 99%
“…Recent reports indicate that PFAA exposure is associated with cardiovascular disease, diabetes, and vitamin D deficiency, but studies in humans have provided contradictory results that require further evaluation of the biological toxicity of PFAAs [ 39 ]. Further studies have reported that, in pregnant African American women, PFAA exposure may affect vitamin D levels [ 40 ] and that perfluorohexane sulfonate (PFHxS) correlates strongly with vitamin D 3 metabolites [ 41 ]. In silico, PFOA bound competitively to the Vitamin D Receptor (VDR), and, indeed, mixtures of PFAAs may also activate the VDR, which has a critical role in the regulation of genes important for the maintenance of calcium homeostasis and immune and endocrine functions [ 42 ].…”
Section: Introductionmentioning
confidence: 99%